1997
DOI: 10.1148/radiology.203.2.9114121
|View full text |Cite
|
Sign up to set email alerts
|

Multileaf collimation in the treatment of the intact breast.

Abstract: Multileaf-collimator blocking for primary breast treatment is similar to conventional blocking, and the transition from one technique to another should be uneventful. The transmission dose to the contralateral breast is decreased with the multileaf collimator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The surface dose was nearly doubled using a tray with or without MLC. Higher surface dose from a MLC with small clearance is often a contraindication to treating breast and head and neck cancer; however, McCormic et al 43 and Dawson et al 44 showed that even for close distance MLCs, surface dose is not a concern.…”
Section: Surface Dosementioning
confidence: 99%
“…The surface dose was nearly doubled using a tray with or without MLC. Higher surface dose from a MLC with small clearance is often a contraindication to treating breast and head and neck cancer; however, McCormic et al 43 and Dawson et al 44 showed that even for close distance MLCs, surface dose is not a concern.…”
Section: Surface Dosementioning
confidence: 99%